Eyelid and Lacrimal Canaliculus Rupture in an Elderly Patient: A Case Report and Management Approach - Kosasih, Bay Hepi; Rima, Anissya; Permana, Muhammad Rizal; Juwita, Oktarina Nila (Universitas Pahlawan Tuanku Tambusai, 2024)
Canalicular lacerations resulting from eyelid or periorbital area injuries are considered ophthalmologic emergencies. This condition transcends age groups and primarily affects the lower canaliculi, potentially leading to canaliculus stenosis and lacrimal dysfunction characterized by epiphora if not promptly addressed. In this medical journal abstract, we present a case study involving an elderly male patient who sustained eyelid and lacrimal canaliculus injuries. The management approach consisted of inserting a silicone tube and using a 6-0 nylon suture for eyelid reconstruction. Notably, the procedure was successful without any complications, resulting in a favorable outcome for the patient. This case underscores the importance of timely intervention and the efficacy of the described surgical technique in addressing canalicular lacerations.